Urea variability in plasma and milk of cows in correlation with the kind of ration consumed - ΜΠΕΛΙΜΠΑΣΑΚΗΣ, Ν. (Journal of the Hellenic Veterinary Medical Society, 2019)
32 cows and 4 types of rations were used in order to calculate the urea level in cow blood plasma and milk, in connection with the type of the ration used. The rations contained different levels of nitrogen substances and starchy foods. From our experiment we found: a) When the starchy foods in the rations were increased, the urea level in the blood plasma and milk was decreased. b) When the nitrogen substances in the rations which had the same amount of roughage foods were increased, the urea level in blood plasma and milk was increased. c) There was a high degree of correlation between the urea level in blod plasma and urea level in milk (r=0,99).